They Persist: Parent and Youth Voice in the Age of Trump. (6th April 2018) - Spinak, Jane M.
Abstract : In recent decades, parents and youth involved in the child welfare and foster care systems have created myriad ways to have their voices heard and their concerns appreciated, including through collective self‐advocacy efforts. New forms of individual and communal advocacy have emerged, including with supportive professionals, that acknowledge the centrality of parents and youth in every decision being made about their lives and about the systems that control their lives. Nevertheless, studies of youth and parent engagement identify the numerous individual and systemic barriers to meaningful participation and self‐advocacy efforts and the challenges to overcoming those barriers. This essay explores how empowered parents and youth can surmount those barriers with the assistance of their professional allies. Ultimately, this individual and communal engagement will strengthen a family‐oriented child welfare system and a more responsive government in these uncertain times. Key Points for the Family Court Community: Parents and youth are developing effective ways to participate in case proceedings and systemic reform efforts in the child welfare and foster care systems. Professional practitioners must understand the advantages and challenges of greater client autonomy and voice in case proceedings and systemic reform efforts. Systemic barriers to parent and youth engagement include poverty and racism, multiple chronic stressors, trauma, and marginalization. Effective parent and youth engagement in case processes and systemic reform efforts can lead to improved individual and familial outcomes and systemic reform.